Highlights from the 2019 international myopia summit on ‘controversies in myopia’ - Wong, Chee Wai; Foo, Li Lian; Morjaria, Priya; Morgan, Ian; Mueller, Andreas; Davis, Amanda; Keys, Drew; He, Mingguang; Sankaridurg, Padmaja; Zhu, Jian Feng; Hendicott, Peter; Tan, Donald; et al. (British journal of ophthalmology, 2021)
Myopia is an emerging public health issue with potentially significant economic and social impact, especially in East Asia. However, many uncertainties about myopia and its clinical management remain. The International Myopia Summit workgroup was convened by the Singapore Eye Research Institute, the WHO Regional Office for the Western Pacific and the International Agency for the Prevention of Blindness in 2019. The aim of this workgroup was to summarise available evidence, identify gaps or unmet needs and provide consensus on future directions for clinical research in myopia. In this review, among the many ‘controversies in myopia’ discussed, we highlight three main areas of consensus. First, development of interventions for the prevention of axial elongation and pathologic myopia is needed, which may require a multifaceted approach targeting the Bruch’s membrane, choroid and/or sclera. Second, clinical myopia management requires co-operation between optometrists and ophthalmologists to provide patients with holistic care and a tailored approach that balances risks and benefits of treatment by using optical and pharmacological interventions. Third, current diagnostic technologies to detect myopic complications may be improved through collaboration between clinicians, researchers and industry. There is an unmet need to develop new imaging modalities for both structural and functional analyses and to establish normative databases for myopic eyes. In conclusion, the workgroup’s call to action advocated for a paradigm shift towards a collaborative approach in the holistic clinical management of myopia.
Published Online First 18 August 2020
Gesehen am 19.01.2023